GAMBARAN PENGGUNAAN APD PERAWAT IGD RSI JEMURSARI SURABAYA PADA MASA PANDEMI COVID-19 - Saraswati Dewi Karina; Ratna Ayu Ratriwardhani; Mursyidul Ibad (Jurnal Kesehatan Masyarakat (Undip), 2022)
Based on data compliance with the use and release of PPE Covid-19 pandemic for emergency room nurses during October to December 2020, the use of PPE decreased from October to November, the release of PPE decreased from November to December. This study aims identify the description of the use PPE for emergency room nurses at Jemursari Islamic Hospital. The study used quantitative descriptive design with cross sectional study approach. The research population nurses in emergency room at Jemursari Islamic Hospital, Surabaya. The sample was 32 respondents using total sampling technique. The data used reports of compliance the use and release of PPE obtained through the PPI team and data knowledge, attitudes and actions towards through distributing questionnaires to respondents using the Descriptive Statistics test. The results showed that the majority of nurses were aged <= 30 years (75%), with a D3 education level (63%) and a tenure of > 4 years (72%). The knowledge and attitudes of emergency room nurses about the use of PPE when working are in the good category, while the behavior of most respondents in the complete category is using PPE by 62.5%. The majority of IGD nurses at the Surabaya Islamic Hospital Jemursari are aged <= 30 years, education level is D3 and working period is > 4 years. Knowledge, attitudes and behavior of nurses in the good category and the majority behave completely in wearing PPE. The agency is expected to maintain training on the use of PPE, tighten supervision and reward disciplined nurses.